2018
DOI: 10.21273/hortsci12906-18
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Opportunities to Promote Water Conservation Practices among Nursery and Greenhouse Growers

Abstract: Nursery and greenhouse growers have an important role to play in conserving water resources. Many technologies are available to help growers conserve water. Yet, within the industry, there may be varying levels of knowledge about a specific strategy, along with inconsistent adoption and continued use. An understanding of these factors can be incorporated into educational programming for this audience. This study evaluated the reported knowledge level of U.S. greenhouse and nursery growers about eight s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 11 publications
2
18
1
Order By: Relevance
“…It is important to understand grower perceptions and attitudes in order to encourage proactive engagement in pro-environmental practices, because behavior change is complex. Current research suggests cognitive indicators, contextual considerations, and multivariate influences focused on factors that relate to risk/gain, culture/demographics, values/beliefs, and specific knowledge all need to be considered in the decision-making process related to emergent technologies and best management practices [12,[17][18][19]. Rogers [15] identified specific characteristics of innovations that can make implementation more attractive.…”
Section: Consumer and Grower Perceptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to understand grower perceptions and attitudes in order to encourage proactive engagement in pro-environmental practices, because behavior change is complex. Current research suggests cognitive indicators, contextual considerations, and multivariate influences focused on factors that relate to risk/gain, culture/demographics, values/beliefs, and specific knowledge all need to be considered in the decision-making process related to emergent technologies and best management practices [12,[17][18][19]. Rogers [15] identified specific characteristics of innovations that can make implementation more attractive.…”
Section: Consumer and Grower Perceptionsmentioning
confidence: 99%
“…Following a quantitative multi-criteria decision analysis with nursery and greenhouse growers where cognitive factors as well as adoption characteristics were studied using structural education modeling and a series of linear and logistic regression data analysis, Warner et al [18] reported that more than half of all growers who had implemented one of eight specific conservation technologies continued to use them, highlighting the educational importance of providing support for initial implementation and continued use. Extension and other professionals can increase the likelihood of adoption by showing growers how new technologies are compatible with their existing systems while emphasizing ease of implementation, financial benefits, and decreased production risk to the operation [21].…”
Section: Consumer and Grower Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water technologies still in use by US nursery and greenhouse growers. Adapted from Warner et al (2018). Percentages correspond to those technologies growers indicated they had adopted in the past and continued to use.…”
Section: How To Use This Informationmentioning
confidence: 99%
“…Sensor-based control systems can optimize irrigation schedules by triggering irrigation systems to replace the water transpired and evaporated from the storage zone (Lichtenberg et al, 2014; while minimizing excessive leaching (Warner et al, 2018), improving flower yield and quality (Oki et al, 2001). By pairing sensors that monitor the environment with sensors that continuously monitor plant transpiration, we can determine how the volume of water required for plant growth fluctuates with environmental and physiological demand (Wheeler et al, 2019).…”
mentioning
confidence: 99%